2016
DOI: 10.1186/s40638-016-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

Passivity-based control of an omnidirectional mobile robot

Abstract: This paper studies passivity-based trajectory tracking control of an omnidirectional mobile robot. The proposed control design is simple to be implemented in practice, because of an effective exploitation of the structure of robot dynamics. First, the passivity property of the prototype robot is analyzed. Then the control system is designed based on the energy shaping plus damping approach. We find that the prototype robot itself has enough damping forces. As a result, only energy shaping is needed in our prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…One can see from Table 1 that the lowest ISI value corresponds to the controller (3.16), (3.17), (4.5). Thus, the comparative analysis has confirmed that the proposed controller (3.16), (3.17), (4.5) provides better performance than that of [24]. Compare also the performances of the controller (3.16)- (3.17) and that obtained in [6] and expressed as follows:…”
supporting
confidence: 58%
See 3 more Smart Citations
“…One can see from Table 1 that the lowest ISI value corresponds to the controller (3.16), (3.17), (4.5). Thus, the comparative analysis has confirmed that the proposed controller (3.16), (3.17), (4.5) provides better performance than that of [24]. Compare also the performances of the controller (3.16)- (3.17) and that obtained in [6] and expressed as follows:…”
supporting
confidence: 58%
“…7. In order to compare the performances, the simulation tests were also performed with the "PD+" like controller proposed in [24] for a simpler robot model: (2) ),…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The system output is given by the pose of the mobile robot (26). It is important to note that even with the inclusion of the anti-windup block to the single neuron architecture (25), the computed control signal is bounded, then such control signal designed for a dynamic system, such as the one for the mobile robot (15) is a feed forward neural control law, which composes a stable system [57][58][59].…”
Section: Control Scheme Using the Adaptive Single Neuron Pid Controllermentioning
confidence: 99%